The Properties of ICEBEAR E‐Region Coherent Radar Echoes in the Presence of Near Infrared Auroral Emissions, as Measured by the Swarm‐E Fast Auroral Imager. Issue 12 (19th December 2021) - Huyghebaert, Devin; St.‐Maurice, Jean‐Pierre; McWilliams, Kathryn; Hussey, Glenn; Howarth, Andrew D.; Rutledge, Paige; Erion, Stephanie
Abstract: For the first time, near infrared (NIR) auroral emissions measured from space have been compared with E‐region coherent scatter. The E‐region coherent scatter observations were obtained by the 49.5 MHz Ionospheric Continuous‐wave E‐region Bistatic Experimental Auroral Radar (ICEBEAR) in western Canada. NIR emissions integrated over 650–1, 100 nm wavelengths were obtained from the Fast Auroral Imager instrument onboard e‐POP on CASSIOPE (now Swarm‐E) with a 1 s temporal resolution (same as ICEBEAR), with the instrument slewed to the center of the ICEBEAR field‐of‐view. The coherent echoes and the NIR emissions are expected to originate below 120 km altitude. The radar spectra indicated that the turbulence was very weak. The location of all coherent echoes corresponded to NIR emission brightness values of more than 250 kR (kilo‐Rayleighs) and less than 1, 250 kR. When the emissions were very bright, the electric fields were seemingly too weak to produce plasma instabilities, explaining why no radar echoes were detected. By contrast, even if the electric field happened to be relatively strong in dark regions, the background plasma densities were too small to generate detectable coherent scatter radar echoes. The Doppler shifts of the coherent scatter spectra were clustered around 465 and ± 250 m/s. These magnitudes did not agree with the quiet 350 m/s ion‐acoustic speed expected from the weaker electric fields that should have prevailed under weak turbulence situations. The unexpected Doppler shifts were potentially due to either unexpected strong electric fields and altitude variations, or ambient km‐size density gradients at 110 km. Plain Language Summary: The aurora occurs when the atmosphere stops energetic charged particles. It is a signature of atmospheric ionization. Emissions in the near infrared (NIR) are known to correspond to electrons stopped near 110 km altitude. When the ionospheric electric field exceeds approximately 20 mV/m the relative drift between ions and electrons below 120 km becomes strong enough that the plasma becomes unstable to a mechanism known as the "Farley‐Buneman instability mechanism." Radars can detect structures generated by this instability. For the results presented here, the 49.5 MHz Ionospheric Continuous‐wave E‐region Bistatic Experimental Auroral Radar (ICEBEAR) radar detected 3 m structures generated by the instability. The Fast Auroral Imager onboard the Swarm‐E satellite provided NIR observations coming from approximately 110 km altitude simultaneously with overlapping radar observations. The results revealed that radar echoes were seen in the region of NIR emissions only if the emissions were between 250 and 1, 250 kR brightness, indicating that under very bright emissions, the auroral electric field was too weak to trigger instability. When the emissions were too faint, the plasma density was too small to warrant detection of structures by ICEBEAR even if irregularities were to be present. The radar data also indicated that turbulence was weak even though the observed Doppler shifts were not what is expected from such situations. Key Points: First time comparisons between Auroral Near Infrared Emissions and E‐region coherent scatter data Coherent E‐region echoes only occur when integrated auroral brightness at 650–1, 100 nm wavelengths is between 250 and 1, 250 kRayleighs For the available data, a vast majority of the E‐region coherent echoes are associated with weak turbulence situations